Paraphayngeal salivary duct carcinoma involving the cavernous sinus - Noppadol Larbcharoensub (2018)
Salivary duct carcinoma (SDC) is a relatively uncommon malignant tumor of the salivary gland derived from the excretory duct reserve cells of the salivary glands. The authors report a case of SDC in a 34-year-old man who presented with trismus and left sided headache, radiologically by a left parapharyngeal mass involving into the left cavernous sinus and histologically by intraductal growth pattern with a cribriform appearance and comedonecrosis. Perineural invasion of the mandibular branch of trigeminal nerve is demonstrated. Clinical and pathologic features with relevant literatures are reviewed.